2019
DOI: 10.3389/fgene.2019.01177
|View full text |Cite
|
Sign up to set email alerts
|

Hypoallergen Peanut Lines Identified Through Large-Scale Phenotyping of Global Diversity Panel: Providing Hope Toward Addressing One of the Major Global Food Safety Concerns

Abstract: Peanut allergy is one of the serious health concern and affects more than 1% of the world’s population mainly in Americas, Australia, and Europe. Peanut allergy is sometimes life-threatening and adversely affect the life quality of allergic individuals and their families. Consumption of hypoallergen peanuts is the best solution, however, not much effort has been made in this direction for identifying or developing hypoallergen peanut varieties. A highly diverse peanut germplasm panel was phenotyped using a rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…This project facilitates genotyping of 10 SNPs for just US$ 1.5 per sample including DNA extraction. To avail this opportunity, ICRISAT has developed and deployed a 10-SNP panel containing diagnostic SNP markers for resistance to rust and late leaf spot as well as high oleic acid (Pandey et al 2019c). So far, this 10-SNP panel has been used to genotype more than 55,000 breeding lines for performing early generation screening in India, Malawi, Mali, Niger, Uganda, Senegal and Ghana.…”
Section: High-throughput and Cost-effective Genotyping Assay With Diamentioning
confidence: 99%
See 1 more Smart Citation
“…This project facilitates genotyping of 10 SNPs for just US$ 1.5 per sample including DNA extraction. To avail this opportunity, ICRISAT has developed and deployed a 10-SNP panel containing diagnostic SNP markers for resistance to rust and late leaf spot as well as high oleic acid (Pandey et al 2019c). So far, this 10-SNP panel has been used to genotype more than 55,000 breeding lines for performing early generation screening in India, Malawi, Mali, Niger, Uganda, Senegal and Ghana.…”
Section: High-throughput and Cost-effective Genotyping Assay With Diamentioning
confidence: 99%
“…Of course, there is a consumer concern for allergenicity issues in many food products, but a good labeling guideline and use of groundnuts with low allergen content could help manage some of the issues. In this regard, recent studies reported ELISA-based protocol to quantify allergens from groundnut seeds (Pandey et al 2019b) which was then successfully used for identification of groundnut lines with low allergen content for Ara h1, Ara h2, Ara h3, Ara h6 and Ara h8 (Pandey et al 2019c). There is substantial variability of these components, thus indicating that the compositions of these beneficial compounds could be enhanced through genetic breeding approaches.…”
Section: Market and Consumer Trendsmentioning
confidence: 99%
“…The same could be said of other aspects, not only of groundnut crop improvement research, but of many other crops. Nevertheless, as shown in this article, ICRISAT together with its partners are doing their best to bridge this disconnect and has already achieved success by integrating genomics in breeding to develop disease resistant (Varshney et al, 2014), high oleate (Janila et al, 2016;Bera et al, 2018), and low allergen lines (Pandey et al, 2019c) among others.…”
Section: Advances In Crop Improvement To Mitigate Groundnut Aflatoxinmentioning
confidence: 99%
“…Since the tetraploid genomes became available in 2019 (Bertioli et al, 2019;Chen et al, 2019;Zhuang et al, 2019), comprehensive genome and functional genomics studies are required for mining the genome-wide allergen genes so that crop improvement approaches can be deployed for developing groundnut varieties with low allergen contents. Most recently, ICRISAT-India developed monoclonal antibody based ELISA protocol that successfully screened diverse set of groundnut accessions identifying five major allergens Ara h 1, Ara h 2, Ara h 3, Ara h 6, and Ara h 8 as well as groundnut genotypes with low allergen contents (Pandey et al, 2019b;Pandey et al, 2019c). The threshold of allergen proteins differ significantly in the allergic population, for example a threshold of 100 µg of Ara h 1 is observed in some populations (Warner, 1999).…”
Section: Advances In Crop Improvement Research On Groundnut Allergensmentioning
confidence: 99%
See 1 more Smart Citation